2013
DOI: 10.1682/jrrd.2012.05.0096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three agility tests with male servicemembers: Edgren Side Step Test, T-Test, and Illinois Agility Test

Abstract: Abstract-Performance-based outcomes such as the T-Test, Edgren SideStep Test (ESST), and Illinois Agility Test (IAT) have been used to assess agility in athletes and nonathletes; however, the reliability and validity of these tests have not been established. The purpose of this study was to establish the reliability and convergent construct validity of the ESST, TTest, and IAT in young, nondisabled, physically active male servicemembers (SMs). Ninety-seven male Active Duty U.S. Army SMs completed the study. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
1
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(173 citation statements)
references
References 25 publications
4
152
1
16
Order By: Relevance
“…There are different methods for measuring changes of direction and speed agility of players in team sports, such as 505 Test (505) [5] and Illinois Agility Test (IAT) [6]. Even though both methods are widely researched and commonly used, the 505 test only considers one COD in 180 degrees, while IAT test considers distances that result in fatigue instead of a quick and explosive response.…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods for measuring changes of direction and speed agility of players in team sports, such as 505 Test (505) [5] and Illinois Agility Test (IAT) [6]. Even though both methods are widely researched and commonly used, the 505 test only considers one COD in 180 degrees, while IAT test considers distances that result in fatigue instead of a quick and explosive response.…”
Section: Introductionmentioning
confidence: 99%
“…The models of agility’s main underlying sub-factors (Jeffreys, 2011; Sheppard et al, 2014; Young et al, 2014, 2015) were specifically based on the empirical approach, while the explanation and application of the agility tests were derived mainly from the following: 1) validity and reliability of indicators that were considered criteria of agility performance; 2) correlations revealed between these indicators and other manifest variables such as the “T” agility test, straight sprint, countermovement jump or skinfold thickness (Gabbett et al, 2008; Hachana et al, 2013; Pauole et al, 2000; Raya et al, 2013). Therefore, the aim of this review was to determine which main factors could quantitatively determine agility performance.…”
Section: Introductionmentioning
confidence: 99%
“…Agility tests can be composed of multiple elements, including acceleration, deceleration and retropulsion, which occur during multidirectional, bidirectional or unidirectional movements [131]. The most commonly used agility tests include a pro agility shuttle [126], t -test [132135], Edgren side-step test [135], zig-zag test [134], the Illinois agility test [134, 135] and the 505 agility test [127, 136–138]. All of these tests are suitable for using in the field because they do not require a lot of space or expensive equipment.…”
Section: Physical Fitnessmentioning
confidence: 99%
“…Some military research includes agility under the heading ‘mobility’, which is an essential element of effective movement around different terrains [139, 140]. A study on U.S. Army personnel found that the t -test, the side step test and the Illinois agility tests were all valid and reliable measures of agility and, therefore, assess mobility [135]. Additional studies on assessments in the U.S. Army and Navy found that the pro agility test can identify changes in military fitness over time and could be used as part of the physical fitness testing process [126, 140].…”
Section: Physical Fitnessmentioning
confidence: 99%